2016
DOI: 10.1136/bjophthalmol-2015-308214
|View full text |Cite
|
Sign up to set email alerts
|

Patients with more severe symptoms of neuropathic ocular pain report more frequent and severe chronic overlapping pain conditions and psychiatric disease

Abstract: Objective To study chronic pain and mental health profiles in patients with dry eye (DE) symptoms, comparing those with high and low levels of neuropathic ocular pain (NOP) complaints. Design Cross-sectional study of 181 patients with DE symptoms (dry eye questionnaire score ≥6) seen in the Miami Veterans Affairs eye clinic. An evaluation was performed consisting of questionnaires regarding DE symptoms, NOP complaints (burning, sensitivity to wind, light and cold/hot temperatures) and pain elsewhere in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 42 publications
2
49
0
Order By: Relevance
“…This study included mild and moderate DE participants (OSDI scores between 12.5 and 31.8) and the results should not be extended to more advanced disease states. In fact, recent data on ocular surface pain suggest that the ocular surface of severe DE patients may respond differently from ocular stimulation than milder forms of the disease …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study included mild and moderate DE participants (OSDI scores between 12.5 and 31.8) and the results should not be extended to more advanced disease states. In fact, recent data on ocular surface pain suggest that the ocular surface of severe DE patients may respond differently from ocular stimulation than milder forms of the disease …”
Section: Discussionmentioning
confidence: 99%
“…The pathways of ocular pain are not well understood; however, it is believed that sensory pathways are altered (neuropathic pain), especially in more severe cases of the disease . The area of neuropathic pain in the eye is rapidly evolving and it has been suggested that those suffering from it also report more chronic and severe pain in other areas of the body . Future studies may take this into consideration when assessing different states of DE disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…The association of DED with CPS has been suggested 13,6567. Vehof et al67 showed a close relationship between DED and chronic widespread pain syndrome.…”
Section: Association With Neurological Problemsmentioning
confidence: 99%
“…4,13 Additional underlying causes include DED, infectious keratitis, recurrent erosions, radiation keratopathy, contact lens wear, and many others as summarized in Table 1. Important co-morbid conditions include, anxiety, 23,24 depression, 2325 and post-traumatic stress disorders. 23,24 …”
Section: Pathophysiology Of Neuropathic Corneal Painmentioning
confidence: 99%
“…Important co-morbid conditions include, anxiety, 23,24 depression, 2325 and post-traumatic stress disorders. 23,24 …”
Section: Pathophysiology Of Neuropathic Corneal Painmentioning
confidence: 99%